The Relationship of Conditional Cash Transfer Receiver Community With Human Resources Development - Puspaningrum, Laila (International Journal Pedagogy of Social Studies, 2021)
The relationship between community participation and human resources development in Desa Cipetir Kecamatan Lebakwangi Kabupaten Kuningan is pivotal to be analyzed, it is worthwhile to improve human resources quality in Desa Cipetir. The objectives of this study are: 1) to know conditional cash transfer receivers’ participation in supporting human resources development; 2) to describe conditional cash transfer encouraging human resources development; 3) to analyze the relationship between conditional cash transfer receivers’ participation and human resources development. This study was held because of community awareness level to participate in establishment is generally low if government assistance does not exist and the quality of human resources is still low, but through conditional cash transfer program, community is encouraged to participate in establishment, especially human resources development which the objective is to improve human resources quality. This study used quantitative approach with correlational descriptive method. The result in this study are: 1) participation level of conditional cash transfer receivers’ participation is high, it is 81,29%; 2) human resources development in Desa Cipetir is high, it is 82,83%; 3) conditional cash transfer receivers’ participation has very strong and positive significant relationship with human resources development in Desa Cipetir Kecamatan Lebakwangi Kabupaten Kuningan.